Geo(anthropo)genic factors affecting the radioactivity in groundwaters from Guarani aquifer, Brazil - Bonotto, Daniel Marcos [UNESP] (2003)
This investigation was carried out within the Paraná sedimentary basin, involved the sampling of 77 pumped tubular wells, and was realized with the puipose of evaluating the radioactivity in the Brazilian part of Guarani (Botucatu-Pirambóia, Tacuarembó, Misiones) aquifer. The radioactivity due to nuclides belonging to uranium and thorium series decay was investigated in terms of the uranium isotopes 234U and 238U, radon (222Rn), and the radium isotopes 226Ra and 228Ra. The obtained results were compared with the maximum permissible concentration limits in drinking water defined by the Brazilian national standard, as well with the guidelines for drinking water quality established by the World Health Organization. The importance of water-rock/soil interactions was considered in order to explain most of the obtained data.